THE AUTHORITY OF MILITARY COURT IN PUNISHMENT OF CORRUPTION ABUSE OF MILITARY HOUSING SAVINGS FUNDS - Hosnah, Asmak ul; Hafidz, Jawade (Jurnal Pembaharuan Hukum, 2024)
The purpose of this research is to determine the authority of the main military court in prosecuting violations of military conscription savings funds. The research method used in this research uses a normative juridical approach. The results of the research stated that the sentence had been carried out by a judge based on the provisions regulated in the Criminal Code and the Corruption Eradication Law. The examination carried out by the judge from the examination at the court of first instance to the appeal level has not been carried out in the form of reverse evidence. This is related to civil interests, namely PLTN, which is a private legal entity related to housing procurement, only carries out its obligations as a company appointed by the Army TWP Organization for the construction of Army housing. The military criminal justice system needs to be developed so that military judges can give civilians the opportunity to provide reverse evidence, which is the NPP's right as a defendant who does not have TNI status.